Studies of pg9/2+ isomers in odd 67-79 as nuclei by deep-inelastic collisions - Hossain, Hossain (2013)
In this paper, we report systematic studies of single particle pg9/2 + isomers in odd 67- 79As nuclei. We have calculated the energies of projectile-like fragments of odd 67- 79As in 76Ge (635 MeV) + 198Pt reactions. The theoretical calculations of projectile like fragments (PLFs) energies are compared with the experimental values. The mean lives, reduced transition probabilities, width of isomeric levels, and Weisskopf hindrance factors in odd 67-79As nuclei are calculated. The excitation levels of 9/2+ and 5/2- state as a function of mass number from odd 67As to 79As nuclei indicate maximum deformation at N=42. The systematic reduced transition probabilities B(M2) of odd 67-79As nuclei are also investigated. The angular distributions of fragments energies of 79As and its counterpart as a function of scattering angles are investigated.